BRAZIL´S CORRECTIONAL SYSTEM: A CLOSER LOOK AT THE PEDRINHAS´PRISON COMPLEX - Malouf, Najla Buhatem (Unoesc International Legal Seminar, 2017)
This article intends to bring up to discussion the tragic incidents with inmate riots and other prison conditions in Pedrinhas´prison complex. It also briefly analyses human rights violations and abuse within the overall Brazilian penitentiary system and the urgent need to tackle the problematic growth of the prison population in Brazil.